The Effect of Good Corporate Governance on Disclosure of Corporate Social Responsibility with Company Size as a Moderating Variable - Putu Renita Sri Naravika, Ida Ayu; Ayu Nyoman Budiasih, I Gusti (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
Banking has many relationships that are directly involved with the community in the form of social responsibility carried out by banking to the community, namely by implementing Corporate Social Responsibility (CSR) programs. Implementation of CSR is a concept that makes companies responsible for social and environmental issues around the company so that they can develop in a sustainable manner. The method used in this research is a quantitative method. The number of observational data is 80 companies with purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). The results show that foreign ownership and institutional ownership have a positive effect on CSR disclosure. Company size has a significant negative effect on foreign ownership and institutional ownership on CSR disclosure.